2022
DOI: 10.3390/molecules27020424
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Immune Cells: A Link to Improve Human Health

Abstract: The use of polyphenols as adjuvants in lowering risk factors for various debilitating diseases has been investigated in recent years due to their possible antioxidant action. Polyphenols represent a fascinating and relatively new subject of research in nutraceuticals and nutrition, with interest rapidly expanding since they can help maintain health by controlling metabolism, weight, chronic diseases, and cell proliferation. Resveratrol is a phenolic compound found mostly in the pulp, peels, seeds, and stems of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 143 publications
0
36
0
1
Order By: Relevance
“…RCs are peculiar cells, equipped with granules containing serotonin and piscidin [ 81 ], a potent antimicrobial peptide [ 82 , 83 , 84 ]. They act via Toll-like receptor (TLR), a type of evolutionarily conserved receptor [ 40 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] activated in response to viruses, bacteria or organic or chemical stress [ 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCs are peculiar cells, equipped with granules containing serotonin and piscidin [ 81 ], a potent antimicrobial peptide [ 82 , 83 , 84 ]. They act via Toll-like receptor (TLR), a type of evolutionarily conserved receptor [ 40 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] activated in response to viruses, bacteria or organic or chemical stress [ 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased MMC associated with histopathological changes is related to oxidative stress leading to aggregation of immune cells [ 32 ]. In addition, the presence in melanomacrophages of lipofuscin or melanin, natural pigments with an antioxidant function like polyphenols and flavonoids [ 92 , 93 , 94 , 95 , 96 ], shows high involvement in the immune response [ 102 ]. A study by Giari et al (2008) showed that RCs increased significantly in number and size in kidney tubules of European sea bass exposed to high concentrations of mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is a polyphenol with anti-inflammatory and antioxidant properties contained in several foods, especially red wine, which is a key element in the Mediterranean food tradition [ 216 , 217 , 218 , 219 ]. Resveratrol acts by reducing the secretion of inflammatory cytokines and inducing apoptosis in keratinocytes via silent mating type information regulation 2 homolog (SIRT1).…”
Section: Natural Compounds As An Alternative Treatment For Psoriasismentioning
confidence: 99%
“…However, its properties appear to be conflicting. Its immune functions are dose-dependent: it induces immunosuppression in high doses, while it stimulates the immune system in low doses [ 124 , 125 ]. It intervenes in the immune system by activating macrophages, T cells, and natural killer (Nk) cells with an antioxidant effect, removing reactive oxygen species (ROS), inhibiting cyclooxygenases (Cox), and thus activating anti-inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%